A redshift-dependent IRX–β dust attenuation relation for TNG50 galaxies. Issue 4 (3rd July 2020) - Schulz, Sebastian; Popping, Gergö; Pillepich, Annalisa; Nelson, Dylan; Vogelsberger, Mark; Marinacci, Federico; Hernquist, Lars
ABSTRACT: We study the relation between the UV slope, β, and the ratio between the infrared- and UV luminosities (IRX) of galaxies from TNG50, the latest installment of the IllustrisTNG galaxy formation simulations. We select 7280 star-forming main-sequence (SFMS) galaxies with stellar mass ≥10 9  M⊙ at redshifts 0 ≤ z ≤ 4 and perform radiative transfer with skirt to model effects of interstellar medium dust on the emitted stellar light. Assuming a Milky Way dust type and a dust-to-metal ratio of 0.3, we find that TNG50 SFMS galaxies generally agree with observationally derived IRX–β relations at z ≲ 1. However, we find a redshift-dependent systematic offset with respect to empirically derived local relations, with the TNG50 IRX–β relation shifting towards lower β and steepening at higher redshifts. This is partially driven by variations in the dust-uncorrected UV slope of galaxies, due to different star formation histories of galaxies selected at different cosmic epochs; we suggest the remainder of the effect is caused by differences in the effective dust attenuation curves of galaxies as a function of redshift. We find a typical galaxy-to-galaxy variation of 0.3 dex in infrared excess (IRX) at fixed β, correlated with intrinsic galaxy properties: galaxies with higher star formation rates, star formation efficiencies, gas metallicities and stellar masses exhibit larger IRX values. We demonstrate a degeneracy between stellar age, dust geometry, and dust composition: z = 4 galaxies with a Small Magellanic Cloud dust type follow the same IRX–β relation as low-redshift galaxies with MW dust. We provide a redshift-dependent fitting function for the IRX–β relation for MW dust based on our models.